Covid in the nursing homes: the US experience. (14th December 2022) - Bjoerkheim, Markus B; Tabarrok, Alex
Abstract: The death toll in nursing homes accounted for almost 30 per cent of total Covid-19 deaths in the US during 2020. We examine the course of the pandemic in nursing homes focusing especially on whether nursing homes could have been better shielded. Across all nursing homes the key predictor of infections and deaths was community spread, i.e. a factor outside of the control of nursing homes. We find that higher-quality nursing homes, as measured by the CMS Five-Star Rating system, were not better able to protect their residents. Policy failures from the CDC and FDA, especially in the early stages of the pandemic, created extended waiting times for Covid-19 tests and slowed attempts to isolate infectious residents. But once infections were widespread, testing would have had to have been much greater to have had an appreciable effect on nursing home deaths. We find, however, that starting vaccinations just 5 weeks earlier could have saved in the order of 14, 000 lives and starting them ten weeks earlier could have saved 40, 000 lives.